Possible Mechanism of Placental Mesenchymal Stem Cell-Derived Neural Cell Transplantation on the Recovery of Neurogenic Bladder Function after Spinal Cord Injury - Yao, Ming; Liu, Guo; Li, Yourui; Song, Hualei (Cellular and Molecular Biology, 2022)
After spinal cord injury, more neurogenic bladder function is caused. The purpose of this article is to investigate the possible mechanism of placental mesenchymal stem cell-derived neural cell transplantation on the recovery of neurogenic bladder function after spinal cord injury. 50 SPF Wistar rats were selected to establish a spinal cord injury rat model and divided into experimental groups and in the control group, 25 animals in each group, the experimental group was transplanted with placental mesenchymal stem cell-derived nerve cells, and the urodynamics and TUNEL positive rate were compared. The results of the study showed that compared with the control group, the maximum bladder capacity and bladder compliance of the experimental group increased significantly (P<0.01), and the bladder basic pressure and urinary leakage pressure decreased (P<0.05). The values of these four items are 2.318ml, 28.892cm H2O, 46.34cm H2O, and 0.1389ml/cm H2O, respectively. It can be seen that the transplantation of neural cells derived from placental mesenchymal stem cells is of great significance for the recovery of neurogenic bladder function after spinal cord injury.